Temperature‐Related Morphological Evolution of MoS2 Domains on Graphene and Electron Transfer within Heterostructures. Issue 15 (2nd February 2017) - Wan, Wen; Zhan, Linjie; Xu, Binbin; Zhao, Feng; Zhu, Zhenwei; Zhou, Yinghui; Yang, Zhilin; Shih, Tienmo; Cai, Weiwei
Abstract : Other than the well‐known sulfurization of molybdate compound to synthesize molybdenum disulfide (MoS2 ) layers, the dynamic process in the whole crystalline growth from nuclei to triangular domains has been rarely experimentally explored. Here, a competing sulfur‐capture principle jointly with strict epitaxial mechanism is first proposed for the initial topography evolution and the final intrinsic highly oriented growth of triangular MoS2 domains with Mo or S terminations on the graphene (Gr) template. Additionally, potential distributions on MoS2 domains and bare Gr are presented to be different due to the charge transfer within heterostructures. The findings offer the mechanism of templated growth of 2D transition metal dichalcogenides, and provide general principles in syntheses of vertical 2D heterostructures that can be applied to electronics. Abstract : A competing sulfur‐capture principle jointly with strict epitaxial mechanism is first proposed for the initial topography evolution of MoS2 domains with Mo or S terminations on the graphene template. The electron transfer between Gr and MoS2 is also experimentally evaluated. The understanding for optimizing the experimental design to synthesize the desirable heterostructures for various applications is provided.